The impact of religious values on social and political change in Tolitoli in the early 20th century - Latief, Juraid Abdul (International Journal for Educational and Vocational Studies)
The interpretation of religious values by social and political elites in the modern social history has significantly influenced the development of political structure at national, regional and global level. Religious values were used effectively to mobilize local people against the western governments in Asia and Africa in the last century. Local political entities in South East Asia also experienced the same political development. Jihad concept fuelled and promoted social and political movements of Imam Diponegoro in Java, Sultan Hasanuddin in Makassar, Panglima Polem in Aceh, and Moro independence movement in Philippine. This research used qualitative approach with the method used is a library study which consist of studies used to collect information and data with the help of various materials available in the library such as documents, books, and  historical stories, and various other references. This research found historical evidences that Haji Hayyun played a significant role politically and socially in Tolitoli, Sulawesi Tengah in the early twentieth century. Although tragically ended, as a figure he successfully used religious sentiment to get support from his followers against the Dutch government in Tolitoli.